Family Matters: Dual Network Embeddedness, Resource Acquisition, and Entrepreneurial Success of Small Tourism Firms in Rural China. (November 2022) - Li, Qiucheng; Zhang, Huanzhou; Wu, Mao-Ying; Wall, Geoffrey; Ying, Tianyu
Small tourism firms (STFs) established and operated by local families can be an engine of sustainable rural tourism. This paper stresses the intimate intertwining of family and business in rural STFs and conceptualizes their entrepreneurial success as a combination of business performance and family well-being. Integrating the resource-based view and network embeddedness theory, relationships among the STF owners' dual social networks (family and industry networks), entrepreneurial resource acquisition, and entrepreneurial success are proposed and tested with a sample of 276 STFs in rural China. The empirical analyses reveal that (1) compared with tangible and knowledge-based resources, the owners' acquisition of psychic resources has the strongest effect on entrepreneurial success; and (2) although industry networks provide more diverse access to entrepreneurial resources, family networks are superior in facilitating psychic resource acquisition, thus are especially important to the entrepreneurial success of rural STFs. Theoretical and practical implications are discussed.